Performance Of Inherent Electrogens In Benthic Sediment Mud At Different Ph Conditions In Microbial Fuel Cell - Pradhan, Binjal; Pradhan, Ranjan (European Scientific Journal, ESJ, 2020)
Comparative measurement of electricity produced by inherent eletrogens in benthic mud that were maintained at different operating pH using microbial fuel cell was studied. A two-chamber microbial fuel cell model with proton exchange membrane was adopted for this study applying electrogene sourced from benthic mud collected from local lake and pond in Ontario. The objective of this study is to investigate the effects of different pH of 6, 7 and 8 maintained within the anode cell in a microbial biofuel cell (MFC) containing microbial communities found in a benthic mud medium over 192 hours. The outcomes of the study demonstrated that in acidic conditions, there was an initial decrease in output whereas an alkaline condition allowed for the acclimatization and eventual increase of electric current and microbial activity of the study period. MFC operated at pH 7 generated consistently higher electric power during the study duration exhibiting ideal conditions for the inherent exoelectrogenic bacteria. On average 249.8 mV of electricity were measured from the MFC with pH 7. The average current density calculated to be 9.76 (±2.02) X 10-5 µA/cm2 . The average power density during the study period was calculated to be 2.49 (± 0.77) X 10-5 µW/cm2